Expression Pattern of SLIT 2 Genes Discriminates Malignant from Benign Canine Mammary Tumours - Saharan, Sandeep; Singh, Prem; Singh, Ajit; Gupta, Rajendra Prasad; Dutt, Ravi (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was conducted to investigate the expression of SLIT2 gene in representative tissue samples of mammary tumours of female dogs (n=10) with the age between 5.0 and 16.5 years brought to Veterinary Clinical Complex, LUVAS, Hisar. Excisional biopsy was taken after surgery of these cases. Histopathological studies confirmed four cases of adenocarcinoma, three cases of benign mixed tumours and two of myoepithelioma and one case of adenoma. Amplification plots and dissociation curves of RT-qPCR were indicative of specific amplification of the canine SLIT 2 gene in all the samples. Further, amplification product of a 160 bp SLIT 2 gene and 120 bp β-actin gene in all the RT-qPCR tubes were visible by 2% agarose gel electrophoresis. Out of 10 tissue samples examined, transcript levels of SLIT 2 genes in all different samples ranged from 1.90 to 84.98. Conclusively, the expression of SLIT 2 genes increased in all canine malignant mammary gland tumours, thereby showing its association with tumour malignancy.